Influences of pre-bending load and corrosion degree of reinforcement on the loading capacity of concrete beams - Tran The Truyen; Tran Thu Minh; Nguyen Xuan Tung; Nguyen Duc Hieu; Vu Ba Thanh; Vo Van Nam (Journal of the Mechanical Behavior of Materials, 2022)
In this article, experimental studies on the flexural behavior of concrete beams with corroded reinforcement were conducted. The beams were subjected to simultaneous different load levels and immersed in NaCl solution for 30 days with accelerated corrosion. A four-point bending test was subsequently carried out to determine the loading capacity of these beams. Experimental data show that the loading capacity of the beam decreases as the level of preload increases. The mass loss of steel bars in the beams increases as the level of preload increases. The loading capacity and steel mass loss of the beams subjected to 0.8 of failure load of the non-corroded beam decrease by 32.7 and 30.3%, respectively. The numerical investigation was also done to evaluate the loading capacity with various corrosion degrees of steel bars.